(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
The samples of soil were collected from 7 locations in Halabja city, in February 2019. The natural radioactivity of the soil samples has been studied using High Pure Germanium (HPGe) detection system. The activity concentration (As) of the natural series; 238U, 232Th and 40K was determined for the samples. The values of As were ranged (45.641 ± 3.252 - 92.862 ± 4.295), (61.287±2.996 - 135.773 ± 18.366) and (227.9 ± 4.874 - 413.0±7.060) Bq kg−1, respectively. The radium equivalent activity (????(????????)) was determined with range (52.006 – 130.518) Bq kg-1. The total absorbed dose rate (????) calculated from the activity concentration of 226Ra, 232Th and 40K in the studied area ranges from 25.53 nGy h-1 to 58.921 nGy h-1. The calculated values of total annual effective dose (????????????????) for the soil samples of the study area ranged from 0.156 to 0.361. Since these values are less than unity, the EC report (European Commission, radiation protection report) concludes that the soil from these areas is healthy and poses no substantial radiological risk to the population.